1457. Escherichia coli Community Acquired Pneumonia. (26th November 2018) - John, Teny Mathew; Deshpande, Abhishek; Haessler, Sarah; Brizendine, Kyle; Yu, Pei-Chun; Imrey, Peter; Rothberg, Michael B
Abstract: Background: Escherichia coli has been thought to be an uncommon cause of community-acquired pneumonia (CAP). Large epidemiological data on E. coli CAP (E-CAP) and its comparison to pneumococcal CAP (P-CAP) are lacking. Methods: A multi-center retrospective cohort study of adult patients (aged ≥ 18 years) admitted to 140 US hospitals with pneumonia and/or sepsis from 2010–2015, included in the Premier Research database. Patients with community-onset infection, antibiotic treatment beginning within the first 2 hospital days, and continued for at least 3 consecutive days were included. Patients were excluded if they had been transferred from another acute care facility, had cystic fibrosis, had a hospital length of stay of 1 day or less, co-existent urinary tract infection, gastrointestinal/ intra-abdominal infection, or simultaneous presence of other CAP pathogens. Pneumonia and sepsis were identified by ICD-9 codes. Results: A total of 13, 165 patients met the inclusion criteria, of which 1, 247 had E. coli CAP. Majority of patients with E-CAP were nonnursing home residents (90.2%, 1, 125/1, 247). 69.3% (864/1, 247) patients with E-CAP presented with"sepsis syndrome' compared with only 48.1% in other Gram-negative CAP and 62.5% in P-CAP. Aspiration pneumonia was diagnosed in 5.9% (73/1, 247) with E-CAP. Blood cultures were positive in 59.9% (748/1, 247) of patients with E-CAP with 84.8% positivity in patients with sepsis syndrome. Patients with E-CAP compared with P-CAP were more likely to require ICU-level care (42.6% vs. 38.2%), mechanical ventilation (19.3% vs. 15.7%), and require vasopressors (21% vs. 13.8%). In-hospital mortality was 14.8% in E-CAP compared with 7.4% in P-CAP. The median cost of hospitalization was great in E-CAP than P-CAP ($12, 420.1 vs. $9, 857.5) Re-admission within 30 days was greater among patients with E-CAP than P-CAP (5.4% vs. 4%). 36.8% of isolates were resistant to fluoroquinolones, 10.4% to ceftriaxone and 18.1% to aminoglycosides. Only 10/1, 247(0.8%) were multi-drug-resistant. Conclusion: E. coli is an important cause of severe CAP, with higher mortality, greater need for ICU-level care, and higher re-admission rates than patients with pneumococcal pneumonia. The rate of fluoroquinolone resistance was high and empiric quinolones should be used with caution for patients who are critically ill due to E-CAP Disclosures: A. Deshpande, 3M: Investigator, Research support; Clorox: Investigator and Speaker's Bureau, Research grant and Speaker honorarium; Merck: Investigator and Speaker's Bureau, Research support.